Program Analysis for the Construction of Libraries of Programming Plans Applying Slicing - Villavicencio, Gustavo (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2000.25923, 2000)
Why the automatic understanding systems of programs based on plan libraries of programs are not of current application in the reverse engineering processes or in the ambient of re-engineering?. Even though the complexity of the algorithms that explore the libraries constitutes one of the principal problems to solve, the construction itself of the plan libraries represents a problem even more crucial. To mount a repository of this type, it is essential to have the professionals that have developed the systems or that accomplish maintenance in the interest area. To date, there exist no reports that describe some technique on how to accomplish analysis of programs oriented to the construction of libraries of programming plans. In the framework of the NEIGHBORS Project currently in execution, a technique based on the automatic comparison of slices is being investigate; this permits the analyst to focus his attention on a meaningful code for the design of program plans, liberating to a large extent the efficiency of the tasks of analysis from the previous knowledge of the applications and from the problems domain. The obtained results until now confirm the feasability of the approach.